Emergency management of children with acute severe asthma requiring transfer to intensive care. Issue 11 (17th June 2010) - Dehò, Anna; Lutman, Daniel; Montgomery, Mary; Petros, Andy; Ramnarayan, Padmanabhan
Abstract : Purpose: Children presenting to emergency departments (ED) with acute severe asthma unresponsive to initial medical therapy may require endotracheal intubation and mechanical ventilation. There is little data on complications during the acute management of children with life-threatening asthma, particularly at hospitals where specialist paediatric staff are lacking. It was hypothesised that a better understanding of complications, particularly associated with intubation and mechanical ventilation, would improve acute management in ED, aid quality improvement initiatives at district general hospitals (DGH) and form the basis for educational interventions from regional paediatric critical care units. Methods: A retrospective case note review was performed for all children referred to a regional intensive care retrieval service with status asthmaticus over a 2-year period. Initial treatment, patient-related factors, indication for endotracheal intubation and the type and occurrence of adverse events during acute management at the DGH were studied. Bivariate and multivariate analyses were undertaken to identify factors associated with the occurrence of complications. Results: 51 (85%) of the 60 children transferred to a paediatric intensive care unit for acute severe asthma required intubation. 36 (70.5%) experienced one or more complications during intubation and in the early phase of mechanical ventilation. The most common complications were hypotension (requiring fluid resuscitation and/or inotropic support) and severe bronchospasm with acute hypercarbia. The indication for intubation significantly affected the chances of a complication occurring during stabilisation. Conclusions: There is considerable morbidity in asthmatic children who are referred to paediatric intensive care. The majority of complications may be anticipated and prevented resulting in improved management at DGH.